Correlation Nutrition Knowledge of Mother’s Curing of Post Sectio Caesarea - Yosin , Esti Pratiwi; Kristianingrum, Dhita Yuniar; Aini, Inayatul; Sandi, Devi Fitria (Jurnal MIDPRO, 2024)
Birth represent the physiologist event. However, if there are complication, action must be taken1. Nutrition is the factors that influence wound curing2. One behavior process is also influenced with knowledge3. The purpose of the research is to identify correlation between the knowledge of nutrition to the curing of post sectio caesarea wound. Design of the research used survey. The independent variable was knowledge about nutrition, the dependent variable was the curing of post sectio caesarea wound. This research used correlation spearman by the value ρ < 0,005. The population was the post sectio caesarea mother on the seventh day who getting birth and control at RSUD Jombang on June 2020. The number of sample was 32 respondents. Sampling used purposive sampling. The data collected by using questionnaire and checklist. The results showed that 17 people (47.2%) experienced good healing, 18 people (50%) had enough, 1 person (2.8%) was lacking. This was influenced by the mother's experience, most of which were first experiences, 23 respondents (23.9%). Less education so that respondents are not good at receiving. Statistical test results obtained p = 0.005 <0.05. The conclusion, there is a relationship between knowledge about nutrition and wound healing after SC with a significance value of 0.005. Increasing one's knowledge can be done by providing counseling on the importance of nutrition and personal hygiene